2022
DOI: 10.1002/jca.21973
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic effects of therapeutic plasma exchange: A concise review

Abstract: Therapeutic plasma exchange (TPE) alters the hemostatic balance. Contributing to TPE's hemostatic effects is the mechanical processing of blood in the extracorporeal circuit, circuit anticoagulant, type of replacement fluid, TPE schedule and number of procedures, TPE timing relative to invasive procedures, and removal of nontargeted components such as platelets, coagulation proteins, and cytokines. Although TPE's hemostatic effects are well established, how it impacts the bleeding risk is not clearly understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 104 publications
0
23
0
Order By: Relevance
“…An area of potential concern for the apheresis practitioner is the type of replacement fluid to be used during TA, notably TPE. The reader should be cognizant of the risk of coagulation factor depletion (especially fibrinogen), particularly after daily TPE use in some clinical settings 12 . Coagulation factor replacement (e.g., plasma or cryoprecipitate supplementation) may be considered in these situations.…”
Section: Methodsmentioning
confidence: 99%
“…An area of potential concern for the apheresis practitioner is the type of replacement fluid to be used during TA, notably TPE. The reader should be cognizant of the risk of coagulation factor depletion (especially fibrinogen), particularly after daily TPE use in some clinical settings 12 . Coagulation factor replacement (e.g., plasma or cryoprecipitate supplementation) may be considered in these situations.…”
Section: Methodsmentioning
confidence: 99%
“…Dilutional coagulopathy occurs when the patients’ plasma is exchanged with albumin or saline [ 1 , 16 ]. However, TPE does not remove single factors but leads to a balanced reduction of pro- and anticoagulant proteins [ 17 ], which might explain the relatively low prevalence of bleeding [ 18 ]. Nevertheless, there is significant uncertainty with regards to both coagulation monitoring during exchange regimens and the cumulative effect of multiple exchange sessions [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Outcome measures used to determine efficacy of fluid replacement were disease specific and none of the three studies showed any benefit of TPE over standard treatment. Randomised control trials are needed to compare the cost‐effectiveness of different TPE fluids, 29 and in particular NS.…”
Section: Discussionmentioning
confidence: 99%